Letter from Carl Duncan to Patricia Whiting, November 7, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan comments on the outcome of local elections, particularly on the deafeat of a propostion that would outlaw obscene materials and conduct.